Charged particle dynamics in GaAs/AlGaAs quantum well - Levinson, Eduard (2019)
In this thesis, I present a study of the magnetotransport (MT) in the quantum wells of GaAs samples in the low magnetic fields. The idea of studying MT in the GaAs quantum wells (QWs) appeared as a result of measurements of HgTe samples. The effects of MT observed in the HgTe samples required strong numerical analysis. Some of the results are presented in Appendix I. We have measured magnetoresistance in local, non-local and Hall configurations during the Ph.D. In addition, I have studied a system response of GaAs samples to microwave (MR) irradiation. The thesis consists of three chapters, five attachments, and five appendixes. In the first chapter, I give a theoretical basis of the magnetotransport in two dimensional electron system (2DES). At the end of the first chapter, I describe different transport regimes which can be observed in 2DES. Samples and experimental setup are described in the second chapter. This chapter provides a description of samples processing, patterns that I used in photolithography, and experimental setup used for this work. In the third chapter of the thesis, I explain MT measurements of GaAs. It is the main part of this work. First, we compared a ballistic model with the experiment. It revealed that electron transport has complicated character, and it is necessary more than one model for be described. We supposed that the electron transport in our samples has hydrodynamic transport besides ballistic. Thus, the experiment was continued to clarify the nature of electron transport in the structures. We performed measurements at local, non-local, and Hall configurations with different current flow directions and arrangements for voltage probes. We observed the dynamic contribution to the electron transport. We also confirmed theoretically predicted Gurzhi effect in our samples. Appendixes consist of supplementary experimental and theoretical. First, consist of MR measurements of HgTe samples and comparison experimental results with theory. Second appendix is about MR measurements of GeP samples. This work was done in collaboration with another laboratory. Third appendix consist of MR measurements of GaAs samples under MW excitation. In the last two appendixes are discussed some questions which appeared during the theoretical work and results analysis. Attachments consist of four articles and one poster presentation. First, is the MR measurements of doped germanium. Second, is the poster about MR measurements in the GaAs with theoretical comparison. Last three attachments are MR measurements of GaAs samples with analysis of the results.